Clinicopathological profile & outcome of critically ill patients suffering from Dengue: Single Centre Experience during COVID Pandemic - Kaniz Fatema; Alimul Haque; ASM Areef Ahsan; Ahmed, Fatema; Debasish Kumar Saha; Madhurima Saha; Suraiya Nazneen; Rozina Sultana; Ishrat Jahan; Taslima Begum; Khandaker Sabbir Ahmed (Bangladesh Critical Care Journal, 2023)
Introduction: Dengue is endemic in our country contributing significantly in morbidity & mortality. This study was conducted to observe the clinic-pathological profile, presentation & outcome of critically ill dengue patients who required Intensive Care Unit admission. Methods: This observational study was conducted in ICU of a tertiary care hospital in Dhaka city from July 2021 to September 2021. Laboratory confirmed cases of Dengue patients admitted in ICU were included in the study. Results: Total patients were 40 with equal male-female distribution. Mean age of the patients was 39.17 ± 13.83 years with most of them (70%) in age group of 18-40 years. Direct admission through Emergency Room (42.5%) was more than transfer-in from indoor of same hospital & other hospitals (35% & 22.5% respectively). There were multiple reasons for ICU admission including hypotension (commonest reason), breathlessness, diarrhoea, abdominal distension, altered level of consciousness etc. Only 13 (32.5%) patients had co-morbidities like DM, HTN etc, and mean age of them was significantly higher than patients without co-morbidities (50.3 ± 13.31, vs 32.23 ± 6.88). Biochemical parameters showed that TWBC count was normal in most patients (n=27, 67.5%), thrombocytopenia was present in 35 (87.5%) patients during admission, hypocalcaemia was present in most patients (90%), liver enzymes were raised in most patients (87.5% & 95% respectively for AST & ALT) and three patients had AKI. Twenty percent patients needed vasopressor support for shock & 5% needed mechanical ventilator support for respiratory failure. Clinical condition was improved in 38 patients & most of them (82.5%) were transferred out from ICU within 6 days. Only two among forty patients expired despite resuscitative efforts. There was no significant difference in the biochemical parameters between survivors & non-survivors. Conclusion: As dengue specific treatment is not yet available, early recognition of the critically ill patients and immediate supportive treatment along with close monitoring in Intensive Care Unit is life-saving for the patients. Bangladesh Crit Care J September 2023; 11 (2): 68-74